2021
DOI: 10.3389/fpsyt.2021.629262
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Workplace Bullying and the Mental Health of Construction Industry Apprentices: A Mixed Methods Study

Abstract: Young Australian males working in the construction industry are twice as likely to take their own lives than other young Australian males. This group is also at high risk for poor mental health and alcohol and other drug related harm. Previous research has indicated a bullying culture within this industry, directed particularly toward apprentices and those new to the industry. This Australian study applied an exploratory sequential mixed methods design to explore issues faced by apprentices, estimate the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 28 publications
9
48
1
Order By: Relevance
“…Therefore, we suggest treading carefully when discussing the previously held assertion that the ACI embodies a culture that encourages increased adherence to traditional masculine norms, above and beyond what is currently experienced in the broader male population. Further research is needed in this space to support this finding, as previous research suggests problematic culture not only for suicidal trajectories but in other contexts such as high levels of apprentice bullying [ 44 ]. Future research may consider comparison across more distinct populations (e.g., construction compared to non-male dominated industries) or across sub-groups within the ACI (e.g., apprentices compared to tradesmen, younger employees compared to older) to create richer understandings.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, we suggest treading carefully when discussing the previously held assertion that the ACI embodies a culture that encourages increased adherence to traditional masculine norms, above and beyond what is currently experienced in the broader male population. Further research is needed in this space to support this finding, as previous research suggests problematic culture not only for suicidal trajectories but in other contexts such as high levels of apprentice bullying [ 44 ]. Future research may consider comparison across more distinct populations (e.g., construction compared to non-male dominated industries) or across sub-groups within the ACI (e.g., apprentices compared to tradesmen, younger employees compared to older) to create richer understandings.…”
Section: Discussionmentioning
confidence: 86%
“…Another study from Australia highlighted that male apprentices working in the construction industry were at particularly high risk of committing suicide, showing poor mental health in general, and turning to alcohol and other drugs. All of these were related to workplace bullying, which many construction industry apprentices were experiencing regularly [ 36 , 37 ]. Additionally, the barrier to seeking help was particularly high in male-dominated sectors due to toxic masculine belief systems that imply self-reliance or the suppression of emotions [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since apprentices have been shown to be a burdened group even in the absence of the COVID-19 crisis [ 34 , 35 , 36 , 37 , 38 , 39 ] and research findings on their state of mental health [ 33 ] and consumption behavior [ 40 , 41 ] during this crisis added to the concern, a qualitative research approach was used to examine what apprentices felt most burdened by during the pandemic and how they dealt with these burdens.…”
Section: Introductionmentioning
confidence: 99%
“…Two-thirds of apprentices consumed alcohol at harmful levels [12], and a quarter of apprentices reported they had used cannabis in the previous month [9]. A recent study found that apprentices used a range of stress management strategies, such as hobbies and exercise, alcohol and drug use, and taking stress home to their partners and families [13]. Their employment-related stress also contributes to apprentices not completing their training, with about half of trade apprentices in Australia dropping out, and many doing so within the first year of training [14].…”
Section: Introductionmentioning
confidence: 99%